STUDI ANALISIS PERAN LANSIA DALAM MENDAMPINGI KORBAN KEKERASAN SEKSUAL PADA REMAJA PUTRI DI KABUPATEN GUNUNGKIDUL - Jacoba Nugrahaningtyas Wahjuning Utami; Tutik Astuti (Universitas Respati Yogyakarta, 2022)
The elderly group (elderly) will be expected to increase from year to year. One of the government's strategies is to increase the active participation of the elderly population. So do not be surprised if childcare is done by grandparents who are elderly still found in Indonesia. In 2020, there will be a decrease in cases of violence against women. But this decline occurred in the pandemic period that allows complaint services to be online, causing complaints not to occur because the victim chooses to tell the family or choose to be silent.Purpose of Research: to find out the presdisposition factors of the elderly accompanying victims of sexual violence in adolescents in the form of family relationships, attitudes and trigger factorsMethodology: This type of research is done descriptively and uses qualitative analysis.Conclusion: There is no relationship between the elderly and adolescent victims of sexual violence, and emotional bonding with the victim that makes the elderly moved to accompany. Predisposing factors in kinship, education and elderly attitudes will influence the decision to accompany adolescent victims of sexual violence.